2023
DOI: 10.3389/fpubh.2023.1080800
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of awareness rate of prostate-specific antigen (PSA) among the general public in China and analysis of influencing factors

Abstract: ObjectiveThis study aimed to evaluate the awareness rate of prostate-specific antigen (PSA) among the general public in China and provide data about prostate cancer (PCa) for related scientific research.MethodsA cross-sectional survey of PSA awareness was conducted in multiple regional populations using an online questionnaire. The questionnaire included basic information, knowledge about PCa, the awareness rate and application of PSA, and future expectations toward applying PSA screening in clinical practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In contrast, this value is lower in Asia and in Africa. A Chinese survey in general population (including males and females) found that 37.9% of the respondents were aware of the PSA test [ 19 ]. These percentages are similar to another Asian study, in which although 96.5% of the 600 Korean respondents knew about PCa only 9.7% of men over the age of 40 recognized the value of PSA as a screening test [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this value is lower in Asia and in Africa. A Chinese survey in general population (including males and females) found that 37.9% of the respondents were aware of the PSA test [ 19 ]. These percentages are similar to another Asian study, in which although 96.5% of the 600 Korean respondents knew about PCa only 9.7% of men over the age of 40 recognized the value of PSA as a screening test [ 20 ].…”
Section: Discussionmentioning
confidence: 99%